Zhao, F., Min, D.Z., Xiang, C.L., Chen, B., Zhou, X.X., Liu, B. & Li, B. (2021) Morphological evidence for the conspecific status of the rediscovered Mimulicalyx rosulatus and M. paludigenus. Phytotaxa 520 (1):106–112. - Zhao, Fei; Min, Dao-Zhang; Xiang, Chun-Lei; Chen, Bin; Zhou, Xin-Xin; Liu, Bing; Li, Bo (Phytotaxa, 2021)
N/A